The Complex Construct of Wellbeing and the Role of Vagal Function - LOWRI WILKIE (Frontiers in Integrative Neuroscience, 2022)
The construct of wellbeing has been difficult to define and has avoided straightforward solutions (Bache et al., 2016). This also makes the topic a fascinating one to reflect on and study. Here we introduce the complex construct of wellbeing, then discuss how the vagus nerve might support the experience of it, before reflecting on some complexities and opportunities arising from a focus on vagal function as target for “inner development” and transformation of the self.